Report on the Three OnLAC-Derived Service Performance Indicators: SPIs 14, 15, and 16 - Flynn, Robert; Miller, Meagan; Vincent, Cynthia (Université d'Ottawa | University of Ottawa, 2014)
This report provides basic information and interpretation on service performance indicators (SPIs) 14, 15, and 16, which, in the new Ontario child welfare accountability framework, are concerned with client well-being and derived from data collected annually by the Ontario Looking After Children (OnLAC) project. The three indicators are SPI 14: Development assets for children in care; SPI 15: Quality of the caregiver-youth relationship for children in care; and SPI 16: Age-to-grade educational performance of children in care. We present data from OnLAC years 10, 11, and 12 (respectively, 2010-2011, 2011-2012, and 2012-2013). For 0-17 year olds, with whom most of the present report is concerned, the annual samples ranged between 6,580 and 6,851 young people in care, with data collected by 41 local Children’s Aid Societies (CASs) in each year. For the analyses in the Executive Summary (Tables B.1-B.3), based on SPI 14 (developmental assets), the sample sizes ranged between 6,732 and 6,930. The results showed, first, that CASs accounted for only a very small portion of the total variation in SPI 14-16 scores. Second, SPI 14 correlated consistently and significantly with SPIs 15 and 16, whereas SPIs 15 and 16 were related only very weakly or not at all. Third, as noted in Table A (next page), of 36 ANOVA or chi square-based comparisons made on SPIs 14-16 between the means or percentages of the female and male youths in care across the three OnLAC years, the females had significantly higher scores on 53% of the comparisons, versus 3% for the males, and the female advantage was especially marked on SPI 16 (92% versus 8%). Also as noted in Table A, of 36 comparisons made between the means or percentages of the First Nations, Métis, or Inuit (FNMI) and non-FNMI young persons in care, the FNMI youths had significantly higher scores on 22% of the comparisons, versus 6% for the non-FNMI youths. The differences tended to be most marked on SPI 16, least marked on SPI 15, and intermediate OnLAC Performance Indicators: SPIs 14, 15, & 16 4 on SPI 14. Finally, in the ANOVAs involving SPIs 14 and 15, only 2 of the 48 ethnicity-by-gender interactions were statistically significant, indicating that ethnicity and gender had largely independent influences on the SPIs.
Keywords: child welfare; performance measurement; ontario looking after children; onlac; child development